Perlindungan Hukum Pemegang Hak Atas Tanah Dalam Sengketa Sertipikat Ganda - Sintasari, Audina (Lentera Hukum, 2015)
Land use without rights is prohibited. Therefore, the issuance of land titles certificate. However, in practice, there is still a circulation of land rights that are not in accordance with the provisions of the law and one of them is the circulation of double certificates in the community. The issuance of the double land title certificate by the land office has resulted in a double certificate of land, which is contrary to the principle of legal certainty and certainty of land rights controlled by individuals, legal entities or institutions. This article examines the form or form of protection and legal remedies for holders of land rights concerning multiple certificate disputes. Based on the literature review, in practice, the legal protection of the holder of land rights is regulated in Article 32 of Government Regulation Number 24 of 1997 concerning Land Registration whereas the legal remedies for land dispute settlement which can be taken by the holder of the aggrieved dual-rights land rights can take the path outside the court / non litigation and judicial/litigation lines. This article concludes with suggestions for real reform of the National Defense Agency's bureaucracy and the enhancement of the quality of its human resources and should know in advance the status of land ownership rights in the event of transactions in the case of transfer of ownership of land so as not to cause problems in the future. KEYWORDS: Legal Protection, Land Dispute, Multiple Certificate.